2020
DOI: 10.1186/s13756-020-00819-1
|View full text |Cite
|
Sign up to set email alerts
|

Etiology and antimicrobial resistance of secondary bacterial infections in patients hospitalized with COVID-19 in Wuhan, China: a retrospective analysis

Abstract: Background A considerable proportion of patients hospitalized with coronavirus disease 2019 (COVID-19) acquired secondary bacterial infections (SBIs). The etiology and antimicrobial resistance of bacteria were reported and used to provide a theoretical basis for appropriate infection therapy. Methods This retrospective study reviewed electronic medical records of all the patients hospitalized with COVID-19 in the Wuhan Union Hospital between January 27 and March 17, 2020. According to the inclusion and exclu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
147
7
14

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(173 citation statements)
references
References 20 publications
(30 reference statements)
5
147
7
14
Order By: Relevance
“…The etiology found here for late-onset VABP in COVID-19 patients resembles the diversity of Gramnegative pathogens typically found in nosocomial pneumonia [25]. Previous cohort studies have reported diverse etiology in COVID-19 confirmed cohorts, with A. baumannii, K. pneumoniae, E. coli and P. aeruginosa as predominant infecting agents [26][27][28]. The species distribution and resistance pattern within individual studies may vary depending on the geographic and local ICU etiology of resistant isolates, study-specific patient recruitment and sample selection, and the treatment history of prior antibiotic exposure in regular VABP patients and COVID-19 patients.…”
Section: Discussionsupporting
confidence: 61%
“…The etiology found here for late-onset VABP in COVID-19 patients resembles the diversity of Gramnegative pathogens typically found in nosocomial pneumonia [25]. Previous cohort studies have reported diverse etiology in COVID-19 confirmed cohorts, with A. baumannii, K. pneumoniae, E. coli and P. aeruginosa as predominant infecting agents [26][27][28]. The species distribution and resistance pattern within individual studies may vary depending on the geographic and local ICU etiology of resistant isolates, study-specific patient recruitment and sample selection, and the treatment history of prior antibiotic exposure in regular VABP patients and COVID-19 patients.…”
Section: Discussionsupporting
confidence: 61%
“…Subcutaneous emphysema was a significant complication, also described in other studies, and has been associated with a poor prognosis [ 21 ]. Most of our patients with subcutaneous emphysema were on NIV, and interestingly, only two had concomitant pneumothorax.…”
Section: Discussionmentioning
confidence: 84%
“…Studies on the interplay between SARS-CoV-2 and type I IFNs confirmed that SARS-Cov-2 infection inhibits type I IFNs production and signaling which increases susceptibility of the host toward secondary bacterial infections [ 67 , 68 ]. The infections include bloodstream infections that are normally caused by coagulase-negative staphylococci, Acinetobacter baumannii , Escherichia coli , [ 69 ], Klebsiella pneumoniae , and Stenotrophomonas maltophilia [ 70 ]. Other viruses that caused respiratory diseases such as rhinovirus and influenza virus also show increased secondary invasion of the airway epithelium lining by pathogenic bacteria and worsening disease progression [ 71 ].…”
Section: Covid-19 and Bacterial Infectionsmentioning
confidence: 99%